SUCCESSES AND CHALLENGES OF ONLINE LEARNING IN FOREIGN COUNTRIES - Yuldasheva F.F. (Journal of new century innovations, 2023)
Annotation: This article illustrates what is the online learning, its importance, what are the advantages and disadvantages of this alternative of education and it is about how much the influence of e-learning increased after the pandemic, challenges and successes it was emerged at universities around the world.